GEOMAP: INOVASI PELAYANAN PUBLIK UNTUK AKSES PETA-PETA KEGEOLOGIAN INDONESIA - Agustin, Fitriani; Edy S, Verry; Gunanto, Dedy; Datanaya, Dimas (PPSDM Geominerba, 2023)
Geomap is an online web application for free accessing geological related maps resulted from geological surveys and field investigations in The Centre for Geological Survey, Geological Agency, Ministry Energy and Mineral Resources. GeoMap can be represented as digital transformation in map services where traditionally map service performed in library as hard copy map sheets. Design thinking method was used to create GeoMap application which focused on problem solving and user orientation. This public service innovation is able to reduce the GeoMap Standard Operational Procedure (SOP) duration from 19 days to less than 2 hours.